Molecular theory of the living cell : concepts, molecular mechanisms, and biomedical applications - Ji, Sungchul (Springer New York, 2012)
This book presents a comprehensive molecular theory of the living cell based on over thirty concepts, principles and laws imported from thermodynamics, statistical mechanics, quantum mechanics, chemical kinetics, informatics, computer science, linguistics, semiotics, and philosophy. The author formulates physically, chemically and enzymologically realistic molecular mechanisms to account for the basic living processes such as ligand-receptor interactions, protein folding, single-molecule enzymic catalysis, force-generating mechanisms in molecular motors, signal transduction, regulation of the genome-wide RNA metabolism, morphogenesis, the micro-macro coupling in coordination dynamics, the origin of life, and the mechanisms of biological evolution itself. Possible solutions to basic and practical problems facing contemporary biology and biomedical sciences have been suggested, including pharmacotheragnostics and personalized medicine.